Experimental Analysis of Rainfall-Induced Instability and Failure Patterns in Loess Fill Slopes - Jinlian Ma; Qian Wang; Xiumei Zhong; Ping Wang; Xiaohui Yang (Advances in Civil Engineering)
Due to the complex terrain and topographical constraints of the Loess Plateau, flat land suitable for engineering construction is extremely limited. To address this issue, filling gullies and leveling land has become a common solution, resulting in the widespread use of loess fill slopes across numerous infrastructure projects. With the increasing frequency of extreme rainfall events worldwide, the stability of these loess fill slopes under rainfall conditions has become critically linked to the safety of engineering structures, as well as to public and property security. This study investigates the failure mechanisms of loess fill slopes subjected to intermittent rainfall using indoor physical model testing. The experiments monitored changes in soil pressure, pore water pressure, and displacement within the slope, alongside observations of crack development to analyze the progression of slope instability. The key results are summarized as follows: (1) The evolution of soil pressure and pore water pressure is significantly impacted by the form and pattern of rainfall. All three monitored parameters (e.g., soil pressure, pore water pressure, and displacement) exhibited consistent macroscopic deformation behaviors. Around the 10th h of rainfall, bulging at the slope toe and minor deformation were observed. By the 25th h, sharp fluctuations and peak values appeared in both soil and pore pressures, accompanied by a sudden displacement increase of approximately 25 mm, signaling large-scale slope sliding; (2) Crack development during intermittent rainfall followed a sequence: surface erosion and expansion, crack initiation and soaking-induced softening at the slope toe, crack propagation and interconnection, and ultimately progressive tensile failure extending from the slope toe to the crest; (3) The failure and instability of loess fill slopes under intermittent rainfall are driven by a combination of rainwater infiltration, erosion, soaking, and wet–dry cycles. The drying period between rainfall events facilitates the expansion and extension of cracks, which subsequently serve as preferential seepage pathways during further rainfall, accelerating water infiltration and triggering slope instability; (4) Owing to the relatively low rainfall intensity used in the model, the observed failure can be classified as a static landslide, which explains the relatively low values of measured soil and pore water pressure throughout the test. These results offer valuable guidance for the design of support systems and drainage infrastructure in loess fill slopes, and provide practical insights for early-warning systems, hazard prediction, and disaster risk reduction strategies.